Evaluation of the performance of the communal Wastewater Treatment Plant (WWTP) in Hegarmanah Village, Cianjur Regency - Khasanah Arinda Nur; Kasih Arwani Noer; Rahayu Lulu Sri; Sari Nita Kurnita (BIO Web of Conferences)
The domestic wastewater treatment system is a building made to treat household waste that can reduce pollution in biological and chemical waste so that the waste does not have a negative impact on the environment. Therefore, it is necessary to ensure that wastewater treatment operates properly and correctly in accordance with the ideal conditions and quality standards according to Permen LHK RI No.P68 / Menlhk / Secretary General / Cum.1 / 8/2016 . Wastewater Treatment Plant (WWTP) Hegarmanah village Cianjur Regency has been built since 2023 until now. Serving 50 families with 196 souls, with the initial plan using aerobic technology but after one year it was changed to use an anaerobic system so it is necessary to evaluate the performance of the WWTP. Along with the growth and development of the human population, since the construction of the Hegarmanah village WWTP, there has certainly been an increase in the waste load on the WWTP. So a performance evaluation is needed to determine the effectiveness of the Hegarmanah village WWTP performance. This study uses a quantitative descriptive approach research method with ob-servation methods and laboratory tests on domestic wastewater which aims to analyze the perfor-mance results of the Hegarmanah village WWTP and test the concentration of quality standard pa-rameters pH, COD, BOD, TSS, Ammonia taken at the inlet and outlet of the Hegarmanah village WWTP. From the results of the study it can be seen that the performance of the WWTP Hegarmanah village Cianjur district is classified as still effective, this can be seen from the decrease in pH at inlet 6.82 and outlet 7.67, BOD at inlet 246 mg/l and outlet 29 mg/l, COD at inlet 737 mg/l and outlet 88 mg/l, TSS at inlet 74 mg/l and at outlet 6 mg/l, ammonia at inlet 0.560 mg/l and outlet 0.0400.